2021
DOI: 10.1002/hyp.14392
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of landscape changes on hydrological variables in the alpine and cold region using hydrological model and remote sensing data

Abstract: Quantifying the impact of landscape on hydrological variables is essential for the sustainable development of water resources. Understanding how landscape changes influence hydrological variables will greatly enhance the understanding of hydrological processes. Important vegetation parameters are considered in this study by using remote sensing data and VIC-CAS model to analyse the impact of landscape changes on hydrology in upper reaches of the Shule River Basin (URSLB). The results show there are differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…A previous study [ 52 ] suggested that there are differences in the precipitation intensity and frequency of precipitation in low-land to alpine areas. Thus, the interpolation method has always been inadequate in the application of precipitation in alpine areas [ 53 ]. Therefore, the improvement of precipitation observation accuracy in the Qilian Mountains is an important basis for future research on precipitation and extreme precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [ 52 ] suggested that there are differences in the precipitation intensity and frequency of precipitation in low-land to alpine areas. Thus, the interpolation method has always been inadequate in the application of precipitation in alpine areas [ 53 ]. Therefore, the improvement of precipitation observation accuracy in the Qilian Mountains is an important basis for future research on precipitation and extreme precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…Land Use/Land Cover (LULC): LULC plays a vital role in many hydrological processes such as infiltration, runoff velocity, evapotranspiration, and soil erosion [66]. The LULC map was derived from Cartosat 1B data (2.5 m resolution) using on screen digitization and selective ground truthing.…”
Section: Soil Erosion Conditioning Parametersmentioning
confidence: 99%
“…The understanding of how the hydrological response co‐evolves with hillslope structure is crucial for the evaluation of how hydrological systems will adapt to changes in climate (Montagne & Cornu, 2010) or anthropogenic disturbances (Cui et al., 2021). Human activities, such as changes in land cover and use, landscape degradation, and anthropogenic climate change, have a profound impact on water quantity, quality, and temporal availability (Bronstert et al., 2002; Jin et al., 2021). Glacier retreat, bark beetle infestations, surface mine closures, land conversion for agriculture, and diverse land use practices are only a few examples which can profoundly influence local hydrology (Goeking & Tarboton, 2020; Haeberli, 2017; Ross et al., 2021; Truong et al., 2022).…”
Section: Introductionmentioning
confidence: 99%